FAKTOR PENENTU REMUNERASI DAN KINERJA : STUDI PEGAWAI UNIVERSITAS MUHAMMADIYAH TANGERANG (Value : Jurnal Manajemen dan Akuntansi, 2018)
Study aims to determine and analyze the determinants of remuneration, such as fairness, feasibility, and merit system on performance. The sample unit used in this research is the employee of Muhammadiyah University of Tangerang. The sampling technique used is 78 random sampling taken from 5 faculties. Analytical technique using path analysis with amos program 22. samples taken amounted to 78 respondents and using questionnaire. The results showed that fairness, feasibility and merit system have an effect on employee performance.Keyword : Keadilan, Kelayakan,  Sistim Merit Remunerasi dan Kinerja